ESL Reading Research Based on Eye Tracking Techniques - Wenlian Zhan; Zhulin Shen (Institute of Advanced Engineering and Science, 2015)
Reading is a complex cognitive process. Through eye tracking techniques the cognitive features can be observed in depth, and therefore a better grasp of the instant cognitive processing of language can be achieved. Compared to traditional methods, the greatest advantage of eye tracking is that is that the reader proceeds with reading coherently and fluently without interrupt and interference, which secures the results in higher ecological validity. This paper is mainly about studies on eye movement features in ESL reading, and particularly illustrates eye movement patterns, the relationship between eye movement and perceptual processing, and eye movement control, aiming at providing some basic evidences for explaining the relationship between eye movement behavior and cognitive processing thus helping to solve some theoretical problems in reading. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.6936